2018
DOI: 10.15406/jnhfe.2018.08.00303
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic index lowering effect of different edible coatings in foxtail millet

Abstract: A study was taken up to test the Glycemic Index (GI) of foxtail millet (Setaria Italica). Six healthy subjects between 22-28 years were selected and informed consent was taken from all of them. White bread was used as the standard food. Test foods used were uncoated foxtail millet and coated foxtail millet prepared in the form of rice (millet was cooked only with water). White bread and all the test foods containing 50g of carbohydrates each were given to the subjects. The coatings used on the foxtail millet w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Consequently, this slows down the intestinal breakdown of food. Millets are known to contain higher levels of protein and fat than milled rice, which decreases their GI [ 27 ]. This results from the decreased efficiency of the small intestine's digestive process caused by many substances, including fat and protein.…”
Section: Reviewmentioning
confidence: 99%
“…Consequently, this slows down the intestinal breakdown of food. Millets are known to contain higher levels of protein and fat than milled rice, which decreases their GI [ 27 ]. This results from the decreased efficiency of the small intestine's digestive process caused by many substances, including fat and protein.…”
Section: Reviewmentioning
confidence: 99%
“…The descriptive, meta and regression analyses revealed that Job's tears, fonio, foxtail, barnyard, and teff were the millets with low mean GI (<55) that are more effective (35-79%) in reducing dietary GI than the control samples. Millets with intermediate GI (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69) are pearl millet, finger millet, kodo millet, little millet, and sorghum which have a 13-35% lower GI than the control with high GI (>69). A meta-analysis also showed that all millets had significantly (p < 0.01) lower GI than white rice, refined wheat, standard glucose or white wheat bread except little millet which had inconsistent data.…”
mentioning
confidence: 99%